A Carding System as an Approach to Increasing the Economic Risk of Engaging in IUU Fishing? - Sumaila, U. Rashid (Frontiers in Marine Science, 2019)
The European Union (EU) instituted a carding system via its EC Regulation 1005/2008 with the goal of incentivizing fish and fish products (fish) exporting countries to the Union to take action to reduce IUU fishing in their waters. This regulation stipulates that the EU will issue warnings, known as a "yellow card", to countries that perform poorly in the effort to end IUU fishing in their waters. Failure to curb IUU fishing will result in a ban in the export of fish to the EU via the issuance of a red card. Here, I ask the following questions: What is the economic risk of being red carded by the EU? Is the economic risk big enough to significantly reduce IUU fishing in a targeted country’s waters? Would the risk be broad enough to result in a significant reduction in IUU fishing globally? What if the two other leading fish importing countries, i.e., the United States and Japan, also institute a similar carding system as the EU? To address these questions, I develop and compute an economic risk index for the carding system. This study suggests that the impact of an EU only IUU carding system could be significant for some targeted countries but its effect globally, with respect to reducing IUU fishing, would be minimal. However, I find that the economic risk to fish exporting countries would increase significantly if the United States and Japan also instituted similar carding systems, which would in turn help to reduce IUU fishing worldwide. This contribution shows that an IUU carding system could contribute significantly to the elimination of IUU fishing provided a critical mass of top fish importing countries participate in such a system.